Surgical Resection of Hepatic Cystic Echinococcosis Impaired by Preoperative Diagnosis - Tomohiko Yasuda; Hiroshi Yoshida; Junji Ueda; Yasuhiro Mamada; Nobuhiko Taniai; Masato Yoshioka; Akira Matsushita; Youichi Kawano; Yoshiaki Mizuguchi; Tetsuya Shimizu; Hideyuki Takata; Eiji Uchida (Case Reports in Medicine)
Cystic echinococcosis (CE) is a rare afferent infectious disease in Japan. This paper reports a case of a hepatic cyst being diagnosed after surgical resection. A 40-year-old Syrian male was admitted for evaluation of a hepatic cyst. Serum antibodies of echinococcosis were negative. Enhanced computed tomography of the abdomen revealed a large cystic lesion, 9 cm in diameter, in the left lateral sector of the liver, which had many honeycomb-like septa and calcified lesions. Magnetic resonance imaging of this lesion revealed high intensity in the T2 weighted image. We preoperatively diagnosed this lesion as cystadenocarcinoma or CE and performed a left hepatectomy. Pathological examination revealed the presence of protoscolices in the fluid of the cysts and led to a diagnosis of this lesion as CE. In conclusion, on seeing patients with huge hepatic cysts who come from an epidemic area, we should consider hepatic CE.